Impact of extraction method on alkaloid content and antioxidant activity of Matricaria pubescens - Hassiba Metrouh-Amir; Nadir Amir (Croatian Journal of Food Science and Technology, 2023)
Matricaria pubescens is a medicinal plant much appreciated by the people of the Saharan regions and widely used to treat many diseases. The present study was devoted to evaluate the effect of extraction technique, pH and nature of solvent on alkaloid content and antioxidant activity of M. pubescens. Alkaloid extraction was carried out by applying two techniques, maceration extraction and Soxhlet extraction, using several solvents at different pH (alkaline chloroform, acid methanol, neutral methanol and neutral ethanol). In the present study, the antioxidant activity of the alkaloid extracts of M. pubescens was evaluated using ferric reducing power, molybdate reducing power, DPPH radical scavenging activity, ABTS radical scavenging activity, β-carotene bleaching assay, hydroxyl radical scavenging activity (assessed by deoxyribose assay and HOSC assay) and oxygen radical absorbance capacity (ORAC). The obtained results show that the extraction rates obtained and the antioxidant activities of alkaloid extracts were affected by the extraction technique, pH and the solvent used. The highest extraction rates were obtained with the ethanolic neutral (Soxhlet) and methanolic acidified (maceration) extracts. The alkaloid extracts of M. pubescens exerted a reducing activity of ferric and molybdate ions. They also showed significant radical scavenger activity against DPPH, ABTS, hydroxyl, and peroxyl radicals. This significant wealth of alkaloids and these various antioxidant activities could justify the traditional use of M. pubescens.